2012
DOI: 10.1089/vbz.2011.0617
|View full text |Cite
|
Sign up to set email alerts
|

Aedes aegypti Susceptibility to Insecticide from Abidjan City, Cote D'ivoire

Abstract: The susceptibility of Aedes aegypti adults of three places in Abidjan city selected for an entomological surveillance of potential arbovirus vectors to permethrin, deltamethrin, lambdacyhalothrin, and propoxur was determined using WHO standard procedures. The wild populations of A. aegypti were susceptible to permethrin, deltamethirn, and lambdacyhalothin. Resistance to propoxur was detected in strains collected at the Autonomous Port of Abidjan and at Koumassi (mortality rate: 77%) but possibly resistance to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…aegypti populations from Dakar during the 2009 dengue outbreak. Our findings are consistent with previous results obtained in Côte d’Ivoire, Cameroon and Burkina Faso [ 21 , 49 , 51 ], although susceptibility to this insecticide is still reported to date in Ae . aegypti in some localities of Congo [ 52 ].…”
Section: Discussionsupporting
confidence: 93%
“…aegypti populations from Dakar during the 2009 dengue outbreak. Our findings are consistent with previous results obtained in Côte d’Ivoire, Cameroon and Burkina Faso [ 21 , 49 , 51 ], although susceptibility to this insecticide is still reported to date in Ae . aegypti in some localities of Congo [ 52 ].…”
Section: Discussionsupporting
confidence: 93%
“…In sub-Saharan Africa some studies have reported resistance from Ae. aegypti to DDT 4% and pyrethroids with a decrease in susceptibility to carbamates and organophosphates compounds (34, 35, 37, 57).…”
Section: Discussionmentioning
confidence: 99%
“…aegypti populations can limit the success of chemical control. Evidence of this resistance was reported in West Africa (3437). Many insecticides belonging to pyrethroids, carbamates, and organophosphates are widely used in Burkina Faso for the control of malaria vectors and from which Anopheles gambiae s.l.…”
Section: Introductionmentioning
confidence: 89%
“…For example, much of sub-Saharan Africa is predicted to be suitable for Ae . albopictus , but records remain patchy [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. Since the worldwide records of each species were compiled, new studies in Africa have reported Ae.…”
Section: Range and Distribution Of Aedes Vectormentioning
confidence: 99%